2016
DOI: 10.1016/j.conbuildmat.2016.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of activated high volume fly ash systems using Na 2 SO 4 , lime and quicklime in mortars with high loss on ignition fly ashes

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 25 publications
5
35
0
1
Order By: Relevance
“…Velandia et al [84] investigated reactivity of different high losses on ignition fly ashes (used as 50% of cement replacement) in the presence of lime and quicklime. They showed that the properties of fly ash, especially content of amorphous phases and grain size, as well as the amount and the type of used activator influence reactivity of fly ash.…”
Section: Mechanical Activationmentioning
confidence: 99%
See 3 more Smart Citations
“…Velandia et al [84] investigated reactivity of different high losses on ignition fly ashes (used as 50% of cement replacement) in the presence of lime and quicklime. They showed that the properties of fly ash, especially content of amorphous phases and grain size, as well as the amount and the type of used activator influence reactivity of fly ash.…”
Section: Mechanical Activationmentioning
confidence: 99%
“…However, in case of steam curing at 60°C the compressive strength was similar as for the nonactivated reference. Velandia et al [84] showed that in case of 50% cement replacement by fly ash, activation of such systems by Na 2 SO 4 gives better compressive strength on early days as compared to activating by lime and quicklime. This relationship was observed mainly in case of fly ashes containing low amount of Fe 2 O 3 ; thus, the authors of Influence of selected activating methods on hydration processes... [84] concluded that the content of Fe 2 O 3 in fly ash affected activation process.…”
Section: Moderate Alkali Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the scarce literature on the effects of Ca 2+ during alkali activation is focused on systems with lowiron content (Yuan et al, 2014;Velandia et al, 2016), whereas appreciable levels of iron will increase the complexity of the mechanisms involved. Daux et al (1997) studied the dissolution of basaltic glasses and observed that Fe species are dissolved and precipitated faster than Si and Al.…”
Section: Introductionmentioning
confidence: 99%